Clinical application of pre-rehabilitation concept on comfort colonoscopy in Chinese elderly patients: a randomised controlled trial - Lun Zhang; Xiaoling Lv; Qin Zhu; Jianying Zhou; Hanlei Huang; Yiqian Huang; Caijuan Si (BMC Gastroenterology)
Abstract Background The concept of pre-rehabilitation has been clinically implemented across various surgical fields; however, studies investigating its application in colonoscopy remain limited. This study aimed to evaluate the effectiveness, safety, and patient satisfaction of the pre-rehabilitation concept in bowel preparation for comfort colonoscopy among elderly Chinese patients. Methods The enrolled patients were randomly allocated into the pre-rehabilitation and control groups. Prior to colonoscopy, patients in the pre-rehabilitation group received supplementary oral administration of ENSURE (Enteral Nutritional Powder) and psychological counseling provided by specialty nurses. The control group received only Polyethylene Glycol Electrolytes Powder. The primary outcome was the quality of bowel preparation, assessed using the Boston Bowel Preparation Scale. Secondary outcomes included the polyp detection rate, incidence of adverse effects, and patient satisfaction. Results A total of 485 patients who were admitted for colonoscopy during hospitalization were included in the analysis. There were no statistically significant differences between the two groups with respect to age, sex, and body mass index (BMI). The Boston total score in the pre-rehabilitation group was significantly higher than that in the control group (P < 0.001). The colon polyp detection rates in the two groups were 78.5% and 67.3%, respectively (P = 0.006). Patients in the pre-rehabilitation group reported higher satisfaction with colonoscopy procedures and experienced a lower incidence of hypoglycemic reactions. Conclusions The combination of additional enteral nutrition supplements and psychological counseling can enhance the quality of bowel preparation, decrease the incidence of hypoglycemia, and improve patient satisfaction. This intervention measure is both feasible and worthy of clinical application and promotion. Trial registration This study was registered in the Chinese Clinical Trial Registry on 14/05/2025 (clinical trial registration number: ChiCTR2500102405). Retrospectively registered.